The Online Education Mode and Reopening Plans for Chinese Schools During the COVID-19 Pandemic: A Mini Review - Cen, Xuanzhen; Sun, Dong; Rong, Ming; Fekete, Gusztáv; Baker, Julien S.; Song, Yang; Gu, Yaodong (Frontiers in Public Health, 2020)
Recently, an unprecedented coronavirus pandemic has emerged and has spread around the world. The novel coronavirus termed COVID-19 by the World Health Organization has posed a huge threat to human safety and social development. This mini review aimed to summarize the online education mode and plans for schools to resume full-time campus study in China during COVID-19. Chinese schools have made significant contributions to the prevention and control of the transmission of COVID-19 by adopting online learning from home. However, normal opening and classroom teaching have been affected. For education systems at all levels, online education may be an effective way to make up for the lack of classroom teaching during the epidemic. To protect staff and students from COVID-19, the timing of students returning to full-time campus study needs to be considered carefully. Reviewing and summarizing of the Chinese education system’s response to the virus would be of great value not only in developing educational policy but also in guiding other countries to formulate educational countermeasures.